Digital Transformation Management: Bibliometric Mapping of Topic Development and New Research Trends - Loso Judijanto; Helda Yusita (Westscience Press, 2026)
This study aims to map the development and intellectual structure of digital transformation management research through a bibliometric approach. Data were collected from the Scopus database using relevant keywords and refined based on document type, language, and subject relevance. A total of selected publications were analyzed using VOSviewer and Biblioshiny to examine publication trends, co-authorship networks, country collaboration, and keyword co-occurrence. The results reveal that digital transformation is the central theme connecting multiple research domains, including artificial intelligence, information management, innovation, and sustainable development. The cluster analysis indicates that the field is characterized by strong integration between technological, managerial, and sustainability perspectives. The overlay visualization shows a shift from general conceptual studies toward more applied and technology-driven topics such as blockchain, internet of things, and data-driven decision-making. Meanwhile, the density analysis highlights that while core topics are well-developed, emerging areas—particularly those related to human and organizational aspects—remain underexplored. This study contributes to the literature by providing a comprehensive overview of the evolution, structure, and emerging trends in digital transformation management research, offering valuable insights for future studies and practical implementation.